Color expression characteristics and physical properties of colored mortar using ground granulated blast furnace slag and White Portland Cement - Jang, Hong-seok; Kang, Hye-seon; So, Seung-young (KSCE journal of civil engineering, 2014)
Colored concrete is an attractive alternative to traditional concrete which has poor esthetic properties, in the view point of architectural designs. White Portland Cement (WPC) and inorganic pigment have been used in colored concrete, but there are some physical problems such as increases in efflorescence, and poor workability and low economics. In this study, color expression characteristics and physical properties of colored mortar using Granulate Ground Blast Furnace Slag (GGBFS) were investigated and compared with general WPC colored mortar. The results show that the addition ratio of GGBFS influences significantly the color value efficiency in color ed mortar. The overall amount of Ca(OH) 2 in the colored mortar using GGBFS was smaller than that of WPC colored mortar, and it was contributed to decreases efflorescence and gave more visible color to mortar. The flow of colored mortar was decreased with mixing inorganic pigments, but increased in proportion to the addition rate of the GGBFS. In addition the strength of colored mortars with GGBFS at the long-term aged (after 28days) was higher than that of the general WPC colored mortar, although its strength was developed slowly at the early ages.